2006
DOI: 10.1002/hlca.200690007
|View full text |Cite
|
Sign up to set email alerts
|

The Lipophilicity Behavior of Three Catechol-O-methyltransferase (COMT) Inhibitors and Simple Analogues

Abstract: The ionization and lipophilicity properties of the second-generation catechol-O-methyltransferase (COMT) inhibitors entacapone (1), nitecapone (2), and tolcapone (3) which share the same nitrocatechol structure but have remarkably different pharmacokinetic profiles are investigated to identify relationships between some of these physicochemical parameters and the blood-brain-barrier (BBB) passage. In addition, the lipophilicity behavior of the simpler, structurally related analogues 4 -11 is studied. Combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…However, recent studies demonstrate that tolcapone can be used with benefit when the liver function is actively monitored (79,80). Although these two compounds share the same pharmacophore, their pharmacokinetic profiles are remarkably different (81). Indeed, studies with rats have shown that tolcapone has a longer duration of action than entacapone and is both a central and peripheral COMT inhibitor, whereas entacapone is essentially a peripheral inhibitor (82)(83)(84)(85).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies demonstrate that tolcapone can be used with benefit when the liver function is actively monitored (79,80). Although these two compounds share the same pharmacophore, their pharmacokinetic profiles are remarkably different (81). Indeed, studies with rats have shown that tolcapone has a longer duration of action than entacapone and is both a central and peripheral COMT inhibitor, whereas entacapone is essentially a peripheral inhibitor (82)(83)(84)(85).…”
Section: Discussionmentioning
confidence: 99%
“…The partition coefficient (Log P) of the ionized form of 32 has been determined to be -0.4 in a mixture of 1,2-dichloroethane-water. 98 The low lipophilicity 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 24 of 32 at physiological pH can also explain its limited passage across the BBB. In addition to its low aqueous solubility and lipophilicity, the enzymatic stability of 32 is also limited.…”
Section: Tight-binding Inhibitorsmentioning
confidence: 96%
“…98,99 At the higher pH values (pH ≥ 5) found in the small intestine, 32 exists in the ionized form, which limits its passage through the intestinal wall. The partition coefficient (Log P) of the ionized form of 32 has been determined to be -0.4 in a mixture of 1,2-dichloroethane-water.…”
Section: Tight-binding Inhibitorsmentioning
confidence: 99%
“…Enzymatic hydrolysis rates were measured as described above and the protective activity of the test compounds for each concentration was calculated as the percentage of ALP activity obtained in the absence of oxidation (considered to be 100%). The antioxidant capacity of test compounds was expressed as pIC 50 (Àlog IC 50 ) and was calculated by curve fitting according to the classical sigmoidal dose-response equation using Prism V4.0 (GraphPad Software, Inc., San Diego, CA). All pIC 50 values were determined in triplicate from at least ten test compound concentrations.…”
Section: Determination Of Antioxidant Activity Of Compoundsmentioning
confidence: 99%
“…The good antioxidant properties to protect proteins from loss of activity induced by peroxyl radicals of entacapone and tolcapone emerged in this work might thus provide an enhanced symptomatic efficacy in the treatment of PD, these compounds being able to pass the blood brain barrier (BBB). 50 On the other hand, the antioxidant properties of nitecapone are not relevant for central nervous system (CNS) protection against oxidative damage since it does not penetrate in the brain. 30,51 Convenience of the Developed Screening Assay to Assess Functional Damage to Proteins…”
Section: Antioxidant Protection Of Alp By Comt Inhibitors: An Examplementioning
confidence: 99%